PENDIDIKAN KELUARGA DALAM MENINGKATKAN PENGAMALAN SHALAT ANAK - Hamidah Hamidah (FORUM PAEDAGOGIK, 2018)
The responsibility of parents for children is as carers, protectors and as educators. In the family parents are responsible for providing prayer education to children. There are a number of things parents can do in increasing the practice of child prayer when at home, that is, giving good example, having time to gather with family, motivating children to diligently study and worship, controlling physical and psychological development activities, not discouraging children want to stand alone, not embarrass children in front of people, not too discriminating and favoritism towards children in the family, and not indulging children, but not good if not caring about them.